Visual cues combined with treadmill training to improve gait performance in Parkinson's disease: a pilot randomized controlled trial. (May 2016) - Schlick, Cornelia; Ernst, Alina; Bötzel, Kai; Plate, Annika; Pelykh, Olena; Ilmberger, Josef
Objective: To evaluate the effects of visual cues combined with treadmill training on gait performance in patients with Parkinson's disease and to compare the strategy with pure treadmill training. Design: Pilot, exploratory, non-blinded, randomized controlled trial. Setting: University Hospital of Munich, Germany. Subjects: Twenty-three outpatients with Parkinson's disease (Hoehn and Yahr stage II–IV). Interventions: Patients received 12 training sessions within five weeks of either visual cues combined with treadmill training ( n = 12) or pure treadmill training ( n = 11). Main measures: Outcome measures were gait speed, stride length and cadence recorded on the treadmill. Functional tests included the Timed Up and Go Test, the Unified Parkinson's Disease Rating Scale and the Freezing of gait-questionnaire. Assessments were conducted at baseline, after the training period and at two months follow-up. Results: After the training period ( n = 20), gait speed and stride length had increased in both groups ( p ⩽ 0.05). Patients receiving the combined training scored better in the Timed Up and Go Test compared with the patients receiving pure treadmill training ( p ⩽ 0.05). At two months follow-up ( n = 13), patients who underwent the combined training sustained better results in gait speed and stride length ( p ⩽ 0.05) and sustained the improvement in the Timed Up and Go Test ( p ⩽ 0.05). Conclusions: This pilot study suggests that visual cues combined with treadmill training have more beneficial effects on gait than pure treadmill training in patients with a moderate stage of Parkinson's disease. A large-scale study with longer follow-up is required.